Pengembangan Media Pembelajaran Pemanfaatan Limbah Sabut Kelapa Untuk Meningkatkan Hasil Belajar Siswa Pada Materi IPAS - Hasibuan, Nurul Fadillah; Muchtar, Zainuddin (Lensa: Jurnal Kependidikan Fisika, 2025)
Suboptimal classroom instruction can make content difficult to grasp and reduce students’ focus and interest, a problem compounded by the limited use of a learning medium. This study aimed to develop a coconut coir waste–based learning medium (Ecowaste) to improve students’ learning outcomes in Integrated Science and Social Studies (IPAS). We evaluated the feasibility, practicality, and effectiveness of the Ecowaste learning medium in Grade V at SDN 200206 Padangsidimpuan using a Research and Development approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Content expert validation reached 92% (“very feasible”), and media expert validation reached 91.4% (“very feasible”). Teacher practicality was 90% (“very practical”), and student responses averaged 86.35% (“very good”). The mean pretest score was 58.25%, increasing to 86.5% on the posttest after using the learning medium, which falls into the “Effective” category. These results indicate that the coconut coir waste–based learning medium (Ecowaste) is feasible, practical, and effective for improving students’ learning outcomes.